2009
DOI: 10.1007/s10354-009-0653-0
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis – rechtzeitig handeln heißt behandeln

Abstract: Rheumatoid Arthritis (RA) is the most prevalent inflammatory joint disease in adults and shows a destructive course in most cases. The outcome of the disease - functional decline and invalidity - necessitates an early therapy. Recent studies demonstrate that the initiation of the treatment with a disease modifying antirheumatic drug (DMARD) treatment within the first three months after the onset of symptoms is crucial for sustained improvement of prognosis as well as therapeutic success and outcome. In the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Because it is best to study TBP-sites genome-wide, we created SNP_TATA_Comparator and applied it to build No. 147 dbSNP of 2016 to predict candidate SNP markers of RA (Chadaeva I. V. et al, 2019) as a cause of disability (Koller and Nobauer-Huhmann, 2009). The robustness of this tool was verified here with the growth of the SNP number, as seen in dbSNP build No.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Because it is best to study TBP-sites genome-wide, we created SNP_TATA_Comparator and applied it to build No. 147 dbSNP of 2016 to predict candidate SNP markers of RA (Chadaeva I. V. et al, 2019) as a cause of disability (Koller and Nobauer-Huhmann, 2009). The robustness of this tool was verified here with the growth of the SNP number, as seen in dbSNP build No.…”
Section: Discussionmentioning
confidence: 70%
“…Rheumatoid arthritis (RA) is an autoimmune disease involving autoantibodies (e.g., anti-citrullinated protein antibodies) and proinflammatory cytokines (e.g., TNF-α and IL-6) that participate in the induction of chronic synovitis and bone erosion, followed by deformity (Smolen and Aletaha, 2015), which are some of the most prevalent causes of disability (Koller and Nobauer-Huhmann, 2009). Currently, it is widely accepted that RA immunopathogenesis is mostly mediated by the mechanisms involving a breakdown of immune tolerance to self antigens that is characterized by an increase in the activity of effector T cells causing RA symptoms (Sarkander et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…UA represents 33-35% of patients in early arthritis clinics, usually as mono-or oligoarthritis. The UA course is variable (mild, chronic, or self-limited disease), and ∼20-50% of patients do not fulfill definite disease classification criteria after 1 year of follow up (6)(7)(8). In our early arthritis cohort (n = 381), we found that 30% of patients met criteria for RA, 10% for SpA and 16% did not fulfill criteria for any specific disease after 1 year of follow up (6).…”
Section: Introductionmentioning
confidence: 94%